Nos reíamos como locas, como locas, como locas… La catástrofe eufórica en Yo era una chica moderna de César Aira. (Altre Modernità, 2013)
César Aira’s Yo era una chica moderna can be read as a metaphorical reconstruction of the social dynamics surrounding the argentine socio-economical crisis culminated at the end of 2001. The national catastrophe is portrayed with an euphoric tone that draws ironically on a literary tradition accustomed to associating popular advance with the monster figure and to focalizing the narrative through his violent point of view, thus communicating a sadistic glee in the very act of destruction. Nevertheless, the euphoria permeating the discourse can be also seen in the perspective of a new alliance between artists and lower classes emerging from the civil society’s spontaneous reaction to the crisis, specifically from a series of collective actions promoting horizontality, participation and solidarity between social groups. Aira’s novel seems to celebrate this unusual sensibility, especially in the literary field, where innovative practices began to diffuse as an answer to the new social demands.